El rol de la escuela en la construcción del desarrollo rural: experiencias argentinas - Natalia Millán (Revista Electronic@ Educare, 2007)
Social processes such as globalization, non territorial productive processes, sprouting of local development and the arising of knowledge society –even in the rural context– bring serious implications for rural education, which has to face a process of modernization and reconstruction in order to avoid the exclusion of current social processes.